Aromatherapy - therapy development at the turn of centuries - Urtnowska-Joppek, Katarzyna (Journal of Education, Health and Sport, 2018)
The term “aromatherapy” means healing with the use of essential oils. At the turn of the century, people were discovering the healing influence of different plants, and then great opportunities that essential oils (which are obtained from those plants) gives. Essential oils are very strong substances that used in diluted form, strictly into the skin or through inhalation process, influence on the whole human organism. With a development of different cultures and civilizations, they gained more applications. Starting from interfering in the religious rituals, by embalming corpses in ancient Egypt, up to the greater flowering of aromatherapy in the XX century in the form known to us. Nowadays, aromatherapy is widely used in the treatment of infectious diseases. In cosmetics and physiotherapy - to relax, strengthen the blood supply of the skin, warming up or cooling the skin and muscles. Fragrances are also popularly used in relieving anxiety, depression, stress or insomnia.